2019
DOI: 10.1029/2019jd030641
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Direct Effect of Aerosols on Meteorology and Air Quality Using Aerosol Optical Depth Assimilation During the KORUS‐AQ Campaign

Abstract: To quantify the impact of the direct aerosol effect accurately, this study incorporated the Geostationary Ocean Color Imager (GOCI) aerosol optical depth (AOD) into a coupled meteorology‐chemistry model. We designed three model simulations to observe the impact of AOD assimilation and aerosol feedback during the KORUS‐AQ campaign (May–June 2016). By assimilating the GOCI AOD with high temporal and spatial resolutions, we improve the statistics from the comparison AOD and AERONET data (root‐mean‐square error: 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 78 publications
1
49
0
Order By: Relevance
“…The weather can also affect the AQI directly, as rainfall reduces atmospheric pollutants. Moreover, COVID-19 can be partly transmitted by aerosols [25], in which there is a close relationship between AQI and aerosols [26]. Yet, no studies have explored the interaction between meteorological factors and AQI with new COVID-19 cases, the mortality rate and recovered rates in the early stages of the population migration control in China.…”
Section: Introductionmentioning
confidence: 99%
“…The weather can also affect the AQI directly, as rainfall reduces atmospheric pollutants. Moreover, COVID-19 can be partly transmitted by aerosols [25], in which there is a close relationship between AQI and aerosols [26]. Yet, no studies have explored the interaction between meteorological factors and AQI with new COVID-19 cases, the mortality rate and recovered rates in the early stages of the population migration control in China.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to satellite observations with sparse spatiotemporal coverages (Ma et al, 2014(Ma et al, , 2015Xue et al, 2019), these ground sites can provide hourly PM2.5 concentrations at high spatial resolution in urban areas. Data assimilation (DA) methods that have been widely used in meteorology can be extended to integrate those continuous observational constraints with chemical transport models (CTMs) (Bocquet et al, 2015;Chai et al, 2017;Gao et al, 2017;Jung et al, 2019;Ma et al, 2019). It has been demonstrated that the capability of several representative DA methods, such as the optimal interpolation (OI) (Chai et al, 2017), 3D/4D variational methods , and the ensemble Kalman filter algorithm (Chen et al, 2019a), can bridge the estimation gaps between observed and simulated results.…”
Section: Introductionmentioning
confidence: 99%
“…these increases corresponded to a local -31.39 W m -2 reduction in solar radiation received at the surface, and reductions in planetary boundary layer height, air temperature, and surface wind speed over land, and a deceleration of vertical transport (Jung et al, 2019). Other studies in East Asia have shown ADE decreasing local shortwave reaching the surface by -20 Wm -2 (Wang et al, 2016), as well as significant changes in surface particulate matter and gas concentrations in response to these radiation changes.…”
Section: Introductionmentioning
confidence: 95%